The mechanical behavior of mortar cement mixing with palm sugar due to exposed to heat (high temperature). Issue 1 (April 2021) - Sari, N P; Olivia, M; Djauhari, Z
Abstract: Mortars will suffer damage if exposed to high temperatures. The selection of palm sugar as an added material for building purposes resistant to high temperatures is the aim of this research. This study provides an overview of the effect of high temperatures on mortar behavior. Preparation of specimens using cube mortar with length of 5 cm and carried out treatment at room temperature for 28 days. Mortar will be furnaceat 250°C, 500°C, 750°C for 3 hours. In normal mortar, hair cracks seen at 500°C has seen this fine cracking indicates the mortar has been damaged. For heating temperatures of 750°C the crack size appears larger and deeper, the color of the mortar turns whiter and brighter, mortar has suffered severe damage. Mortars containing palm sugar 0.1%, 0.3% and 0.5% of the weight of cement did not experience cracking at 75°C, but only visible increase in pore size. The pore size is enlarged due to the gas pressure coming out of the cement matrix due to heating. Mortar with additional palm sugar still has a compressive strength of 50% at high temperatures 750°C.